PENGARUH BUDAYA ORGANISASI DAN MOTIVASI TERHADAP KINERJA KARYAWAN PT ANUGRAH ARGON MEDICA JAKARTA - Ratno; Nuridin (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2017)
The purpose of this study is to know how the influence of organizational culture and motivation on the performance of employees of PT. Anugrah Argon Medica Jakarta. The research method used is Explanatory Analysis approach that explains the causalistic relationship between variables. Sampling technique using random sampling samples. Data analysis technique used is quantitative statistical method by looking for validity and reliability test data, correlation, regression, coefficient of determination and hypothesis test. The results of this study found that the relationship and significant influence between organizational culture variables and motivation on employee performance PT Anugrah Argon Medica Jakarta between variables with F test, where F arithmetic is bigger than F table (139,574> 3,150), Conclusion: There is significant influence which can be explained with result obtained from R square is 0,823 meaning that variable of organizational culture and motivation contributed 82.3% to employee performance variable PT. Anugrah Argon Medica Jakarta, while the rest of 17.3% donated another variable that is not researched.